120k views
0 votes
Complete the work shown to find a possible

solution of the equation.

(x-5)2 +5 = 2

(x+5)-3

(x - 5)2 = (-37

172

A possible solution of the equation is

User Bonanza
by
6.3k points

2 Answers

5 votes

Answer:

x = 14

Step-by-step explanation:

the expression takes the form of a radical surd. to solve a radical surd we need to isolate the expression with the root from those not under the root sign

first;

this a surd, so

to eliminate the root we need to multiply it by an expression that will take it away,

since a root is the same as a power of half ()^1/2, then multiplying a half by two will make it one

we need to square both sides to eliminate the root

x -5 = (-3)^2

make x subject

x = 9 + 5

x = 14

User Bharat Biswal
by
5.7k points
4 votes

Answer:

x = 14

Explanation:

the expression takes the form of a radical surd. to solve a radical surd we need to isolate the expression with the root from those not under the root sign

first;


(x-5)^(1/2) this a surd, so


(x-5)^(1/2) =2-5

to eliminate the root we need to multiply it by an expression that will take it away,

since a root is the same as a power of half ()^1/2, then multiplying a half by two will make it one

we need to square both sides to eliminate the root

x -5 = (-3)^2

make x subject

x = 9 + 5

x = 14

User Clee
by
6.3k points